Comparing bird sightings between grassland and marsh habitats at a rehabilitated wetland in Gauteng Province, South Africa - JACQUES BOTHA; NATALIE S. HAUSSMANN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Botha J, Haussmann NS. 2023. Comparing bird sightings between grassland and marsh habitats at a rehabilitated wetland in Gauteng Province, South Africa. Biodiversitas 24: 3536-3542. Wetlands, including rehabilitated wetlands, form important feeding and nesting sites for a large range of bird species. The restoration of degraded wetlands is therefore important from a bird biodiversity perspective and bird surveys are needed in such systems. However, bird counts typically differ both spatially (e.g., between different habitats within the wetland) and temporally (e.g., between different seasons or times of the day). This study compared bird sightings at a rehabilitated wetland in the Gauteng Province of South Africa between marsh and grassland sections of the wetland and between morning and afternoon sessions. A total of 47 bird species were sighted at the wetland, including a number of species that have been listed as declining. Whereas more species were sighted in the marsh habitats of the wetland than the grassland habitats, differences in the number of sightings between habitats depended on the time of day. Thus, although there were no differences in the number of sightings between morning and afternoon sessions at the marshes, the number of sightings was higher in the afternoons than in the mornings at the grasslands. We therefore, first caution against comparing bird counts, in general, between studies conducted at different times of the day. More importantly, however, our results highlight the importance of not only conserving natural, pristine wetlands but also rehabilitated wetlands to create habitats for declining bird populations in transformed environments such as urban settings.